When do soccer players experience the most demanding passages of match play? A longitudinal study in a professional team - Oliva-Lozano, J. M.; Martinez-Puertas, H.; Fortes, V.; Muyor, J. M. (Research in Sports Medicine, 2023)
This study analysed the periods in which the most demanding passages (MDP) of play occurred during professional soccer matches, considering different criterion variables and investigating the effect that the playing position had on the MDP-of-play occurrence for each criterion variable. The MDP of play were calculated based on five criterion variables: distance covered (DIS), sprinting distance (SPD), high-metabolic load distance (HMLD), and the total of high-intensity accelerations and decelerations (ACCHIGH and DECHIGH). The results showed that the first period of the match (0'-15') was the interval with the highest frequency (i.e., the greatest % of cases) in which the players achieved the MDP of play for all the variables (DIS= 38.9%; SPD= 28.4%; HMLD= 37.7%; ACCHIGH= 54.3%; DECHIGH= 48.8%). The playing position had no significant effect on MDP-of-play occurrence in any variable (likelihood ratio, LR= 15.88-32.05; p > 0.05; effect size, ES= 0.01-0.04), except for the DIS covered (LR= 32.05; p= 0.04; ES= 0.05), in which the most frequent MDP for the full backs occurred within the second period of the match (15'-30'). In conclusion, the first periods of the matches usually elicited the MDP of play and these periods need to be trained to prevent injuries and optimize performance.